COMPARISON OF THE EFFECTIVENESS OF FERMENTED TIWAI ONIONS AND LANANG ONIONS ON CHOLESTEROL LEVELS IN SPRAGUE DAWLEY HYPERCHOLESTEROLEMIA RATS - Utami, Kurniati Dwi; Wahyuningrum, Diah Retno; Naimatur, Rizqi (Jurnal Kesehatan Tambusai, 2025)
This study was a pure experimental study using a control group. The experimental animals used were two-month-old Sprague Dawley rats. The four groups of rats were given a high-cholesterol diet with the addition of egg yolk to the feed for two weeks. After the rats experienced hypercholesterolemia, the rats were divided into four groups. The first group was the control group given distilled water. The second group was given simvastatin at a dose of 15 mg/kgBW. The third group was given fermented shallots at a dose of 200 mg/kgBW, and the fourth group was given fermented shallots at a dose of 200 mg/kgBW. Each group consisted of five rats. The results of the ANOVA test showed a significant difference in cholesterol levels between groups with a p value = 0.00. The Tukey HSD further test showed a difference in mean HDL between the control group and the group given simvastatin. However, no significant difference was found in cholesterol levels between the groups given fermented shallots and fermented shallots. The groups given fermented shallots and lanang shallots had lower mean cholesterol compared to the control and simvastatin groups. The conclusion of this study is that the administration of fermented tiwai and lanang onions both showed effectiveness in lowering blood cholesterol levels in rats with hypercholesterolemia, as effective as simvastatin. This finding shows the potential of fermented onions as an alternative herbal therapy in managing high cholesterol.